STUDI PERTUMBUHAN MANGROVE PADA KEGIATAN REHABILITASI HUTAN MANGROVE DI DESA TANJUNG LIMAU KECAMATAN MUARA BADAK KABUPATEN KUTAI KARTANEGARA - Adhi Alwidakdo, Zikri Azham dan Legowo Kamarubayana (Universitas 17 Agustus 1945 Samarinda, 2014)
The experiment was conducted in the village of Tanjung Limau, Muara Badak Sub District of Kutai Regency, East Kalimantan Province. The purpose of the study was to determine the success of mangrove planting activity in the study area in the mangrove forest, and to identify factors that affect the rehabilitation of mangrove forests in study area. Data was collected by creating a transect along 100m of land rehabilitation at three different locations based on the characteristics puddle. Observations was carried out to observe and measure the height and diameter of the plant. Data were recorded and measured at each transect include plant data (type of plant, number of living plants, plant height and growing conditions of the plants healthy). Based on the observation and calculation of the percentage of growing plants was conducted on 20 plots, from mangrove rehabilitation activities carried out in 2009, in 2010 gained a growing percentage of the average of mangrove plants is ±78.18%. While the results of crop assessment carried out in 2011 acquired the mangrove plants growing percentage average is ±66.40%. From the comparison of measurements in 2011 with the results of measurements made in this study, there was a decrease in the percentage of mangrove plants grow on average is equal to ± 11.78%. Based on the observations and calculations of the percentages obtained transect mangrove plants growing on average at 46%. Based on these results it can be concluded that the success rate of rehabilitation of mangrove forests growing percentage decline in the number of mangrove plants. From the results of measurements obtained in the field of plant height and diameter high average in each lane is as follows pathway 1 is the average height of 2.28 m and a diameter of 4.48cm, 2.61m and the second path average diameter average 4.03cm and the third lane average height of 1.91meters with an average diameter of 5.62cm. High variation of different mangrove plants.